Serum cortisol concentration in the Colombian creole horse (2016)
ABSTRACT: Cortisol is indicative of adaptation to physiological factors, disease and environmental stress in equines. Cortisol recently gained attention for its prognostic value in critical disease and as an indicator of fi tness and athletic performance. Objective: To determine baseline serum cortisol (SC) morning concentrations in the Colombian creole horse (CCH). Methods: Blood serum was taken from 62 CCH of both genders with and average age of 8.8 years (± 5.3), which were clinically healthy and had diff erent performance levels. Results: The overall SC average determined by sandwich ELISA was 13.3 ± 7.4 mg/dL. No signifi cant diff erences were attributed to gender, age, or performance. Conclusion: This concentration can be used as a reference value for CCH maintained in low physical activity.